Solution techniques for elementary partial differential equations - Constanda, Christian (Boca Raton, FL CRC Press, Taylor & Francis Group, 2016)
Solution Techniques for Elementary Partial Differential Equations, Third Edition remains a top choice for a standard, undergraduate-level course on partial differential equations (PDEs) Making the text even more user-friendly, this third edition covers important and widely used methods for solving PDEs. New to the Third Edition. New sections on the series expansion of more general functions, other problems of general second-order linear equations, vibrating string with other types of boundary conditions, and equilibrium temperature in an infinite strip. Reorganized sections that make it easier for students and professors to navigate the contents. Rearranged exercises that are now at the end of each section/subsection instead of at the end of the chapter. New and improved exercises and worked examples. A brief Mathematica® program for nearly all of the worked examples, showing students how to verify results by computer. This bestselling, highly praised textbook uses a streamlined, direct approach to develop students' competence in solving PDEs. It offers concise, easily understood explanations and worked examples that allow students to see the techniques in action.
"A Chapman & Hall book."
Prof. Lorna Almocera (Recommending faculty) - Bookfair 2019
Includes bibliographical references and index.
Keywords: Differential equations, Partial